Complement C3d is not associated with axial spondyloarthritis and magnetic resonance imaging changes at the sacroiliac joint. (3rd September 2022) - Nygaard, A; Hendricks, O; Loft, AG; Christiansen, AA; Brandslund, I; Jurik, AG; Schiøttz-Christensen, B
Abstract : Objective: To investigate the associations between complement C3d and inflammatory and structural changes by magnetic resonance imaging (MRI) at the sacroiliac joints (SIJ) suggestive of axial spondyloarthritis, according to the Assessment of SpondyloArthritis international Society (ASAS) criteria, in patients with low back pain. Method: This was a cross-sectional study of patients referred to the Spine Centre of Southern Denmark owing to unspecified low back pain (Spines of Southern Denmark cohort). The patients were divided into three groups: group 1: patients fulfilling the ASAS criteria for axial spondyloarthritis (axSpA, n = 96); group 2: patients with either a positive MRI of the SIJ and no spondyloarthritis features, or a negative MRI of the SIJ but positive human leucocyte antigen-B27 and one spondyloarthritis feature (non-axSpA, n = 38); group 3: patients with unspecified low back pain for > 3 months (control group, n = 82). Complement C3d was measured with double-decker rocket immunoelectrophoresis and evaluated in relation to the group division and baseline findings by SIJ MRI. Results: In total, 184 C3d analyses were performed. The mean ± sd level of C3d was 33.8 ± 8.1 AU/mL. There were no differences in C3d levels between the three patient groups, mean values being: axSpA = 34.3 ± 7.9 AU/mL, non-axSpA = 33.5 ± 6.9 AU/mL, and controls = 33.4 ± 9.2 AU/mL. The level of C3d was not related to MRI findings. Conclusions: In these patients, complement C3d was not associated with active or structural SIJ changes on MRI suggestive of axial spondyloarthritis.